Acid-base transport in pancreas—new challenges - Novak, Ivana; Haanes, Kristian A.; Wang, Jing (Frontiers in Physiology, 2013)
Along the gastrointestinal tract a number of epithelia contribute with acid or basic secretions in order to aid digestive processes. The stomach and pancreas are the most extreme examples of acid (H+) and base (HCO3-) transporters, respectively. Nevertheless, they share the same challenges of transporting acid and bases across epithelia and effectively regulating their intracellular pH. In this review, we will make use of comparative physiology to enlighten the cellular mechanisms of pancreatic HCO3- and fluid secretion, which is still challenging physiologists. Some of the novel transporters to consider in pancreas are the proton pumps (H+-K+-ATPases), as well as the calcium-activated K+ and Cl- channels, such as KCa3.1 and TMEM16A/ANO1. Local regulators, such as purinergic signalling, fine-tune and coordinate pancreatic secretion. Lastly, we speculate whether dys-regulation of acid-base transport contributes to pancreatic diseases including cystic fibrosis, pancreatitis and cancer.